1999
DOI: 10.1007/s004490050707
|View full text |Cite
|
Sign up to set email alerts
|

Studies on production of griseofulvin

Abstract: Griseofulvin is an antifungal antibiotic and is used for the treatment of mycotic diseases of human, veterinary and plant systems. It is synthesised by many species of Penicillium. The exploitation of fermentation process plays a vital role in the industrial applications. This leads to techno-economic feasibility of the processes. The present review mainly discusses on the production of griseofulvin in soil, in plants and by various micro-organisms. This communication also summarises the various factors which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In contrast, it was showed that maximum antibiotics production was obtained at acidic pH (Reddy &Ranganathan, 1985;VenkataDasu and Panda, 1999;Jichenget al, 2008). It has been reported that maximum production of bacitracin and other antibiotics occurred at alkaline pH (Basilioet al, 2003).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, it was showed that maximum antibiotics production was obtained at acidic pH (Reddy &Ranganathan, 1985;VenkataDasu and Panda, 1999;Jichenget al, 2008). It has been reported that maximum production of bacitracin and other antibiotics occurred at alkaline pH (Basilioet al, 2003).…”
mentioning
confidence: 99%
“…Also environmental factors like incubation temperature, pH and incubation time were found to have profound influence on antibiotic production (Srinivasan et al, 1991;VenkataDasu and Panda, 1999;Sujathaet al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of griseofulvin could be due to its planar structure and spatial configuration [ 72 ]. In fact, griseofulvin is an antibiotic fungicide and is now used for the treatment of human mycotic diseases, in veterinary and plant system [ 73 ].…”
Section: Metabolites From Marine Fungimentioning
confidence: 99%
“…The recent literature on 1 for activity against cancer and suppression of hepatitis C virus replication, in conjunction with the influx of patents for analogues of 1, indicate the expanding interest in this class of compounds . Production of 1 is well established via industrial fermentation processes . Our interest was to examine cultures that biosynthesize 1 for two complementary reasons.…”
Section: Introductionmentioning
confidence: 99%